"ÁLL TRÁDES, THEIR GEAR AND TACKLE AND TRIM": THEOLOGY, COGNITIVE NEUROSCIENCE, AND PSYCHONEUROIMMUNOLOGY IN TRANSVERSAL DIALOGUE: with Pat Bennett, "'Landscape Plotted and Pieced': Exploring the Contours of Engagement between (Neuro)science and Theology"; Pat Bennett, "'Things Counter, Original, Spare, Strange': Developing a Postfoundational Transversal Model for Science/Religion Dialogue"; and Pat Bennett, "'Áll Trádes, Their Gear and Tackle and Trim': Theology, Cognitive Neuroscience, and Psychoneuroimmunology in Transversal Dialogue.". Issue 1 (17th February 2019) - Bennett, Pat
Abstract: This third of three articles outlining a different approach to science/religion dialogue generally and to engagement between theology and the neurosciences specifically, gives a brief account of the model in practice. It begins by introducing the question to be investigated—whether the experience of relational connection can affect health outcomes by directly moderating immune function. Then, employing the same threefold heuristic of encounter, exchange, and expression used previously, it discusses how the transversal model set out in these articles has been used to investigate this question and to develop a theoretical physiological model for the proposed link between relationality and health.